A vasculature-centric approach to developing novel treatment options for glioblastoma. (1st February 2021) - Wirsching, Hans-Georg; Roth, Patrick; Weller, Michael
ABSTRACT: Introduction: Glioblastoma is invariably deadly and is characterized by extensive vascularization and macrophage-dominant immunosuppression; nevertheless, anti-angiogenesis has so far failed to prolong overall survival of patients. Regardless of the problems in clinical development, the rationale for the application of anti-angiogenics in glioblastoma remains. Areas covered: Resistance to anti-angiogenics is discussed, including vessel co-option and amplification of hypoxic signaling in response to vessel destruction. The modulation of GSC and tumor-associated macrophages by dysfunctional tumor vessels and by hypoxia are outlined. Pharmacologic approaches to sensitizing glioblastomas to anti-angiogenics and evidence for the cooperation of anti-angiogenics with immunotherapies are summarized. Database search: https://pubmed.ncbi.nlm.nih.gov prior to December 12, 2020. Expert opinion: Despite drawbacks in the clinical development of vascular endothelial growth factor A (VEGF)-targeted agents, there is still rationale for the use of anti-angiogenics. The better understanding of vascular co-option and adverse effects of blood vessel destruction guides to improve strategies for vascular targeting. The pivotal role of the vasculature and of angiogenic factors such as VEGF for the induction and maintenance of immunosuppression in glioblastoma supports the use of anti-angiogenics in combination with immunotherapy. Proinflammatory repolarization of perivascular and perinecrotic tumor-associated macrophages is probably paramount for overcoming treatment resistance to virtually any treatment.